Pengaruh Penggunaan Bahan Ajar Handout Terhadap Hasil Belajar Siswa Pada Elemen Estimasi Biaya Konstruksi XI TKP di SMK Negeri 1 Kediri - Moch Ndaru Wicaksono; Djoni Irianto (Jurnal Kajian Pendidikan Teknik Bangunan, 2023)
This study aims to (1) assess students' learning achievement on the element of Construction CostEstimation by using handout teaching materials, as well as evaluating the learning achievement of studentswho do not use handout teaching materials on the same element (2) identify differences in learningoutcomes between students who use handouts and students who do not use handouts on the element ofConstruction Cost Estimation. This research uses a quantitative approach with experimental methods. Themethod used is a quasi-experiment with a research design of nonequivalent control group design. Thisresearch adopts a quantitative approach by applying experimental methods, by applying a quasiexperimental research design known as nonequivalent control group design. The experimental group andcontrol group were selected using purposive sampling technique. The results of descriptive statisticalanalysis showed that students who used handouts obtained an average result of 81.47, while students whodid not use handouts obtained an average result of 72.60. Based on the normality prerequisite test usingthe Saphiro-Wilk assisted SPSS v25 program, the experimental class pretest results were 0.71, theexperimental class posttest results were 0.59, the control class pretest results were 0.52, the control classposttest results were 0.82 so that all data has been tested normally distributed because the significancevalue ? 0.5 so that it can be continued with parametric tests. Based on the homogeneity test using thelevene assisted SPSS v25 program, the value based on mean 0.104 ? 0.5 so that the data is homogeneous.Based on hypothesis testing using independent sample t-test assisted by SPSS v25 sig value (2-tailed) 0.000< 0.5, it is concluded that Ho is rejected and Ha is accepted. So, there are differences in learning outcomesbetween students who use handouts and students who do not use handouts that affect the use of handoutson student learning outcomes.